2013
DOI: 10.1016/j.asr.2013.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the fluids mixing enclosure system for life science experiments during a commercial Caenorhabditis elegans spaceflight experiment

Abstract: The Student Spaceflight Experiments Program (SSEP) is a United States national science, technology, engineering, and mathematics initiative that aims to increase student interest in science by offering opportunities to perform spaceflight experiments. The experiment detailed here was selected and flown aboard the third SSEP mission and the first SSEP mission to the International Space Station (ISS). Caenorhabditis elegans is a small, transparent, self-fertilizing hermaphroditic roundworm that is commonly used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…However, compared to the air volume in the + air conditions, these bubbles are negligible and thus cannot explain why some -air conditions outperformed the + air conditions in the FME-tubes. The previously reported experiments with C. elegans similarly found that chance largely dictated whether the nematodes survived long-term storage in the FME tubes (Warren et al, 2013). Morokuma et al (2017) concluded that the optimal condition for 30-day survival of intact planarians at 20 • C was a 50-50 airto-water ratio and that using 100% water and no air resulted in complete lethality of intact planarians within 5 days.…”
Section: Lack Of Oxygen and Air To Water Ratiomentioning
confidence: 92%
See 3 more Smart Citations
“…However, compared to the air volume in the + air conditions, these bubbles are negligible and thus cannot explain why some -air conditions outperformed the + air conditions in the FME-tubes. The previously reported experiments with C. elegans similarly found that chance largely dictated whether the nematodes survived long-term storage in the FME tubes (Warren et al, 2013). Morokuma et al (2017) concluded that the optimal condition for 30-day survival of intact planarians at 20 • C was a 50-50 airto-water ratio and that using 100% water and no air resulted in complete lethality of intact planarians within 5 days.…”
Section: Lack Of Oxygen and Air To Water Ratiomentioning
confidence: 92%
“…Generally, such a long transportation time is not ideal for biological experiments. It has been previously emphasized that late loading and early retrieval are optimal to maximize organismal health for life science experiments conducted in space (Hughes-Fulford, 2004; National Research Council of the National Academies, 2011; Warren et al, 2013). Travel time was considerably shorter in the non-SSEP planarian ISS experiments, with launch occurring within 12-14 or 31 h for the Gorgiladze (2008) and Morokuma et al (2017) studies, respectively.…”
Section: Extended Storage At 4 • Cmentioning
confidence: 96%
See 2 more Smart Citations
“…To facilitate this activity, learners can be directed to the Student Spaceflight Experiment Program, which provides details of past and ongoing experiments using NanoRacks hardware that has been used on-board the ISS (http://ssep.ncesse.org/about-ssep/). This also allows them to consider flying an actual experiment, for example, as done by a US High School student (Warren et al, 2013) and by Canadian Secondary School students (Graveley et al, 2018).…”
Section: Activity 3: Spaceflight Hardwarementioning
confidence: 99%